The multiple faces of police identity in Wales: A case study in public order policing - Michael Harrison (Policing: A Journal of Policy and Practice, 2023)
This article explores how policing identities shape and inform understanding and practice within public order (PO) policing. Of particular focus is how police use and apply their national identity as a means of explaining their PO policing approach. The study was based in South Wales, UK and findings are drawn from a qualitative multi-methodological approach with the regional police force. I identified that officers drew upon a stereotypical version of Welsh identity to explain their approach to PO policing that was largely characterised as friendly and interactive. Officers claimed that it was their reflexive instinct to engage in this way because this was simply a manifestation of their Welsh identity and character. While this was an important characteristic and source of pride for officers, I argue that this identity appeared to mask, or in some cases enable, PO policing that had a more traditional focus of law and order.